2020
DOI: 10.5435/jaaos-d-19-00834
|View full text |Cite
|
Sign up to set email alerts
|

Occupation-related Cervical Spine Disease in Orthopaedic Surgeons

Abstract: Introduction: Musculoskeletal injury can substantially affect orthopaedic surgeons and productivity. The objective of this study was to assess occupation-related neck pain and cervical radiculopathy/myelopathy among orthopaedic surgeons and to identify the potential risk factors for injury. Methods: An online survey was sent to orthopaedic surgeons via their state orthopaedic society. The survey consisted of items related to orthopaedic practices, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Similarly, the prevalence of both back and neck pain in these groups was greater than expected based on the reports from previous studies of orthopaedic surgeons in the literature, which determined the prevalence of work-related MSK pain to be between 35% and 60%. 3 In our survey, respondents with back pain, neck pain, or both most commonly attributed their pain to poor posture, with the second most common reason being work-related injury. The combination of poor posture and work-related injury accounted for 60% of all back pain cases and 72% of all neck pain.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, the prevalence of both back and neck pain in these groups was greater than expected based on the reports from previous studies of orthopaedic surgeons in the literature, which determined the prevalence of work-related MSK pain to be between 35% and 60%. 3 In our survey, respondents with back pain, neck pain, or both most commonly attributed their pain to poor posture, with the second most common reason being work-related injury. The combination of poor posture and work-related injury accounted for 60% of all back pain cases and 72% of all neck pain.…”
Section: Discussionmentioning
confidence: 85%
“…most frequently reported. [1][2][3][4] In an attempt to alleviate these work-induced MSDs, a variety of ergonomic interventions have been studied for their efficacy. A clear benefit to these interventions has been established for short-term outcomes, but the long-term effects are less clear.…”
mentioning
confidence: 99%
“…Trainees, in contrast, experienced a nominal increase in pain over the course of their cases. The observation that pain or physical fatigue increases with age is a ubiquitous one 33–35 . Although the attendings included in our study are relatively early in their rhinology careers (mean age 45), rhinology is a unique otolaryngology subspecialty when considering the sustained and immobile posture its surgeries demand 36,37 .…”
Section: Discussionmentioning
confidence: 96%
“…The observation that pain or physical fatigue increases with age is a ubiquitous one. [33][34][35] Although the attendings included in our study are relatively early in their rhinology careers (mean age 45), rhinology is a unique otolaryngology subspecialty when considering the sustained and immobile posture its surgeries demand. 36,37 These static postures are not only maintained throughout surgery, but often throughout the entirety of a surgeon's professional life.…”
Section: Discussionmentioning
confidence: 99%
“…While all surgeons have been found to have an increased risk of sustaining work related MSK disorders, recent studies have shown that the orthopaedic surgeon is at an even increased risk[ 2 , 6 - 8 ]. Repetitive and constantly forceful surgical tasks have been identified as the major contributing factor to their increased prevalence in orthopaedic surgeons.…”
Section: Introductionmentioning
confidence: 99%